Genetic polymorphisms of manganese superoxide dismutase, NAD(P)H:quinone oxidoreductase, glutathione S-transferase M1 and T1, and the susceptibility to drug-induced liver injury - Huang, Yi-Shin; Su, Wei-Juin; Huang, Yi-Hsiang; Chen, Chih-Yen; Chang, Full-Young; Lin, Han-Chieh; Lee, Shou-Dong (Journal of hepatology, 2007)
Drug metabolizing enzymes may be related to drug-induced liver injury (DILI). Manganese superoxide dismutase (MnSOD), NAD(P)H:quinone oxidoreductase (NQO1), and glutathione S-transferase (GST) are important drug metabolizing enzymes. We aimed to elucidate the relationship between genetic polymorphisms of these enzymes and the susceptibility to DILI. A total of 115 patients with DILI and 115 drug-, sex-, and age-matched controls were enrolled. Their genetic polymorphisms of MnSOD, NQO1, GSTM1, and GSTT1 were assayed. Sixty-three (54.8%) of DILI patients were incriminated to anti-tuberculosis drugs. Subjects with a mutant C allele (T/C or C/C genotype) of MnSOD had a higher risk of DILI than those with MnSOD T/T genotype, both in overall drugs studied (adjusted OR: 2.44, 95% C.I.: 1.38–4.30, P = 0.002), and in sub-category of anti-tuberculosis drugs (adjusted OR: 2.47, 95% C.I.: 1.13–5.39, P = 0.02). In addition, subjects carrying GSTM1 null genotype had increased risk of anti-tuberculosis DILI (adjusted OR: 2.23, 95% C.I.: 1.07–4.67, P = 0.03). The MnSOD mutant C allele may increase the susceptibility to DILI, and GSTM1 null genotype may be related to anti-tuberculosis drug-induced hepatotoxicity. Determination of the MnSOD and GSTM1 genotypes may help identify patients at high risk for DILI.